Ansofaxine Hydrochloride inhibits hepatocellular carcinoma growth and enhances targeted therapy through the EGFR/MAPK pathway - He, Yongfei; Tao, Qiang; Mo, Shutian; Chen, Meifeng; Wang, Jicai; Zhai, Hang; Hong, Shengjie; Gao, Qiang; Zhang, Guangquan; Han, Chuangye; Shi, Xianjie (Frontiers in Oncology, 2025)
BackgroundHepatocellular carcinoma (HCC) is a common tumor that endangers health. Depression will affect the therapeutic effect of HCC, and depression and HCC promote and influence each other. Ansofaxine Hydrochloride is a novel antidepressant, and its anti-HCC effect remains to be confirmed.ObjectivesThis study aimed to investigate the effect of Ansofaxine Hydrochloride on HCC and its molecular mechanism.MethodsThe potential targets and signaling pathways of Ansofaxine Hydrochloride against HCC were obtained by network pharmacology, and the key targets were explored by molecular docking techniques. Hepatocellular carcinoma cells were treated with different concentrations of Ansofaxine Hydrochloride, and the effects of Ansofaxine Hydrochloride on the biological function of hepatocellular carcinoma cells were evaluated by CCK8, migration, invasion, and clonal formation tests. Subsequently, a subcutaneous hepatocellular carcinoma mouse model was established to evaluate the effect of Ansofaxine Hydrochloride on the growth of hepatocellular carcinoma tissue in vivo, and an enzym-linked immunosorbent assay was used to detect the levels of dopamine (DA) and 5-hydroxytryptamine (5-HT) in peripheral blood. HE and immunohistochemical staining were used to detect the pathological changes of tumor tissue and the types and proportions of macrophages. Finally, the expression levels of key genes in the EGFR/MAPK pathway were detected by Reverse Transcription Real-time Quantitative analysis.ResultsThere are 87 common drug-disease targets between Ansofaxine Hydrochloride and HCC, including EGFR, GRB2, and SRC, which are mainly involved in EGFR, MAPK, and PI3K/AKT signaling pathways. Molecular docking showed that Ansofaxine Hydrochloride has good binding activity to EGFR, GRB2, and other key targets. In vitro experiments showed that Ansofaxine Hydrochloride has significant inhibitory effects on proliferation, migration, invasion, and clonal formation of HCC cells. In vivo experiments showed that Ansofaxine Hydrochloride has a synergistic effect of enhancingLenvatinib anti-HCC, enhancing peripheral blood DA level, promoting M1 macrophage infiltration, and enhancing immune anti-tumor effects, and is associated with the reduction of EGFR/MAPK pathway-related genes.ConclusionOur study suggests that Ansofaxine Hydrochloride has anti-HCC and immunomodulatory effects, with the EGFR/MAPK pathway as a potential key mechanism of action.